A Grand Theory of STIFIn Personality: Basic Functions Theory Revisited - Poniman, Farid; Amalia, Niqya (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to propose a new theory of personality that can lead to a holistic description of the mechanism of thinking and decision-making of an individual. The central discussion of this proposal is to provide descriptive answers to various basic questions. The concept of this theory does not use the traits or behavioral approach, but it uses a perspective from genetics, neuroscience, biopsychology, and basic function theory. The recent studies on personality are still focused on the determination of personality traits and the application of the roles played by each personality, whereas the most important role of these recent studies is that they should be able to provide a grand theory. In this paper, the main discussion will be focused on providing concepts and changing several definitions that can directly explain phenomena that are in accordance with natural conditions.